Apresentação (Presentation) - Weinstein, José; Muñoz, Gonzalo; Louzano, Paula (Revista Eletrônica de Educação, 2019)
Apresentação do Dossiê "Liderança Educacional". Presentation of the "Educational Leadership" dossier. Introducción del dossier "Liderazgo Educativo" Keywords: Educational leadership Palavras-chave: Liderança educacional Palabras claves: Liderazgo educativo